Colorectal cancer in patients under the age of 40 years: experience from a tertiary care centre in the Czech Republic. Issue 6 (2nd November 2017) - Kocián, Petr; Whitley, Adam; Blaha, Milan; Hoch, Jiří
Abstract: Introduction: Colorectal cancer (CRC) in young patients is not an uncommon disease. Reports on its behaviour in young patients are conflicting. The aim of this study was to investigate patient and tumour characteristics, treatment and prognosis of this disease. Methods: Our study group comprised all patients under the age of 40 years treated with CRC at the Department of Surgery at Motol University Hospital in Prague between the years 2005 and 2015. Results: Thirty-eight patients under 40 years of age diagnosed with CRC were included in the study. Five patients had Lynch syndrome and six had first-degree relatives with CRC. There were 22 rectal tumours. All but four patients underwent resection of the primary tumour, all patients received chemotherapy and 13 patients received biological therapy. Disease recurrence occurred in 25.8%. Five-year survival was 47.9%. Advanced disease and adverse histological subtypes were identified as poor prognostic factors. Conclusions: Colorectal cancer in young patients has a high incidence of predisposing conditions, aggressive histological features and advanced disease. Young patients are of a good state of health and thus should receive aggressive therapy. Clinicians should pay more attention to symptoms of CRC in young patients to be able to initiate early treatment.